Heterogeneity - Allenby, Greg M. (Henry Stewart Talks, 2010)
Panel structure data, Heterogeneity and priors, Hierarchical linear model, Priors, Adaptive shrinkage, Heterogeneous logit model, Random effects with regressors, Heterogeneous logit, Running rhierBinLogit, Data(bank), Sample observations, Distribution of heterogeneity for selected part-worths, Extensions